Korelasi Antara Sistem Pengendalian Kualitas dan Komitmen Organisasi pada Karyawan - Satrio Cahyono putro; Farel Muhammad Fawzi; Anna Marina (Journal of Innovative and Creativity, 2025)
This study aims to analyze the correlation between quality control systems and organizational commitment among employees using a qualitative literature review approach. In the face of global competition, organizations must implement quality control systems that not only ensure product or service standards but also strengthen organizational structure and employee commitment. The study finds that effective quality control—through procedural clarity, employee participation, and continuous evaluation—helps foster a conducive work environment. This positively influences the formation of organizational commitment, especially in affective, normative, and continuance dimensions. Literature reviews highlight that organizational culture and leadership style are also vital in enhancing employee loyalty and emotional attachment to the organization. Moreover, active employee involvement in quality systems cultivates a sense of ownership and reinforces psychological contracts. The practical implication of this research is that integrating quality strategies with human resource management should be an organizational priority to build long-term, sustainable commitment.